2001
DOI: 10.1002/bmc.59
|View full text |Cite
|
Sign up to set email alerts
|

Hybridation of different chiral separation techniques with ICP‐MS detection for the separation and determination of selenomethionine enantiomers: chiral speciation of selenized yeast

Abstract: Enantioseparation and determination of selenomethionine enantiomers in selenized yeast was investigated using chiral separation techniques based on different principles, coupled on-line to inductively coupled plasma mass spectrometry (ICP-MS) for selenium-specific detection. High performance liquid chromatography (HPLC) on a beta-cyclodestrin (beta-CD) column, cyclodextrin-modified micellar electrokinetic chromatography (CD-MEKC), gas chromatography (GC) on a Chirasil-L-Val column, and HPLC on a Chirobiotic T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
(17 reference statements)
0
23
0
Order By: Relevance
“…Mendez et al [99] reported on the use of CD-modified MEKC for the separation of selenomethionine enantiomers when derivatized with naphthalene-2,3-dicarboxal-dehyde (NDA). A new analytical method was developed for enantioselective separation of DL-amino acids labeled with N-fluorenylmethoxycarbonyl-L-alanyl-N-carboxyanhydride (FMOC-L-Ala-NCA).…”
Section: Chiral Micellar Electrokinetic Chromatography (Cmekc)mentioning
confidence: 99%
“…Mendez et al [99] reported on the use of CD-modified MEKC for the separation of selenomethionine enantiomers when derivatized with naphthalene-2,3-dicarboxal-dehyde (NDA). A new analytical method was developed for enantioselective separation of DL-amino acids labeled with N-fluorenylmethoxycarbonyl-L-alanyl-N-carboxyanhydride (FMOC-L-Ala-NCA).…”
Section: Chiral Micellar Electrokinetic Chromatography (Cmekc)mentioning
confidence: 99%
“…This was the first report in which the use of a mixture of b-CD and sodium taurodeoxycholate as chiral selectors in combination was described for the optical resolution of selenomethionine and its derivatives by MEKC. The same authors also improved this method by coupling on-line CD-MEKC to inductively coupled plasma MS (ICP-MS) [116]. The latter approach was successfully applied to the chiral separation of selenium and D-and L-selenomethionine content determination in selenized yeast.…”
Section: Amino Acids In Pharmaceutical Formulationsmentioning
confidence: 95%
“…In a couple of reports Méndez et al [115,116] have described the optimal experimental conditions (10 mM 35 mM sodium borate pH 9.5 1 150 mM SDS Pharmaceutical products (2-Naphthoxy) acetyl chloride amino acids [119] borate, 30 mM phosphate buffer, pH 7.0, 30 mM b-CD, 50 mM taurodeoxycholate, and 50 mM SDS) to obtain the optical separation of racemic CBI-selenomethionine [115], the most active component in the formulation of nutritional supplements commercially available for human consumption. Since selenomethionine is chiral in nature and individual enantiomers usually play different roles in living organisms, optical resolution of selenomethionine into its D-and Lenantiomers is of great interest for nutritional purposes.…”
Section: Amino Acids In Pharmaceutical Formulationsmentioning
confidence: 98%
“…Table 1 summarizes the recent developments in precapillary derivatization procedures. From Table 1 it becomes obvious that most procedures for derivatization of the amino function aim to increase the sensitivity of the assay of these compounds in various biological matrices and for various purposes, such as chiral separations [12][13][14][15][16][17][18]. Sometimes, the samples have been obtained by microdialysis [19,20].…”
Section: Precapillary Derivatizationmentioning
confidence: 99%